Assessment of the Quality of Health Facilities & Infrastructure to Support District Regional and City Planning Facilities - Putra, Rahmat; Sidabutar, Yuanita FD; Indera, Edi; Raymond, Raymond (Journal La Sociale, 2023)
Health facilities are a kind of public infrastructure essential for enhancing community health standards. According to statistical data from the city of Batam, the population of the Nongsa Keluran Batu Besar sub-district was 29,198 in 2020. The majority of respondents perceived the quality of medical personnel services for the general public in Batu Besar Village as satisfactory, evidenced by 50% of respondents. The quality of administrative services for the general public in Batu Besar Village was also deemed satisfactory, as indicated by 45% of respondents. Furthermore, the quality of pharmacist services for the general public in the Batu Besar sub-district was regarded as moderately satisfactory, supported by 47.5% of respondents. The quality of BPJS services for the general people in the Batu Besar sub-district is commendable. This is substantiated by the proportion of responses, which is 52.5%. The level of nursing services for the general people in the Batu Besar sub-district is commendable. This is evidenced by the number of replies, which is 70%. A majority of respondents, 65%, perceived the equipment facilities for the general public in Batu Besar Village as satisfactory, while 60% regarded the room facilities as reasonably good. A majority of respondents, constituting 40%, perceived the public parking facilities in Batu Besar Village as highly satisfactory.